Pemberdayaan Kreatif Masyarakat Melalui Pembuatan Ecobrick untuk Pengurangan Sampah Plastik - Rivaldo Armada Putra; Rindi Metalisa; Gilang Vabio; Muhammad Iqbal; Nur Hikmah; Nurfiza Nurfiza; Azzahra Annida Putri; Nadila Zulfa; Rara Mulyunika; Ranisha Armellia; Sela Selfia Ag (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
Managing plastic waste, which continues to increase, is a global challenge that requires sustainable solutions. One approach that can be applied is community empowerment through making ecobricks. Ecobricks are a method of managing plastic waste by using plastic bottles as containers to fill non-organic waste, thereby producing environmentally friendly building materials. This research aims to identify the impact of community creative empowerment through an ecobrick making program in the context of reducing plastic waste in the local environment. The methods used in this research include a participatory approach through training, counseling and direct observation in the community. The research results show that community involvement in making ecobricks not only contributes to reducing the volume of plastic waste, but also increases environmental awareness and community creativity. In addition, this program has a positive impact on local economic development through the potential use of ecobricks as an alternative construction material. In conclusion, community empowerment through making ecobricks is an effective step in overcoming the problem of plastic waste while empowering communities in a sustainable manner.